2010
DOI: 10.1002/ppul.21293
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life protocol in the early asthma diagnosis in children

Abstract: IntroductionAsthma is considered an important problem in children and influences on their everyday functioning. This study was concerned with the impact of asthma on the health‐related quality of life (HRQOL) of newly recognized pediatric asthma patients and their parents.MethodsPatients were identified by a general respiratory survey. HRQOL was assessed by self‐report measures: disease‐specific questionnaire for children, the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) and generic for parents—the Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 26 publications
7
26
4
Order By: Relevance
“…However, Merikallio et al [6] demonstrated in their study that a short-time QOL can be obtained from children, but for longitudinal observation parents’ information seems to be more adequate. In opposite to the study of Farnik et al [7], we found significant positive correlation between PAQLQ and PACQLQ in all domains. We did not observe any significant correlation between clinical parameters in children and asthma quality of life in parents, which stay in accordance with previous studies [7].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, Merikallio et al [6] demonstrated in their study that a short-time QOL can be obtained from children, but for longitudinal observation parents’ information seems to be more adequate. In opposite to the study of Farnik et al [7], we found significant positive correlation between PAQLQ and PACQLQ in all domains. We did not observe any significant correlation between clinical parameters in children and asthma quality of life in parents, which stay in accordance with previous studies [7].…”
Section: Discussioncontrasting
confidence: 99%
“…In opposite to the study of Farnik et al [7], we found significant positive correlation between PAQLQ and PACQLQ in all domains. We did not observe any significant correlation between clinical parameters in children and asthma quality of life in parents, which stay in accordance with previous studies [7]. We interpret these results as clinical parameters such as FEV1 and FeNO being weak indicators of disease severity especially in short-time observation of mild asthma.…”
Section: Discussioncontrasting
confidence: 99%
“…For the impact of infantile asthma on QoL, for example, studies have shown that providers should ask both children and their caregivers about the effects of asthma on the child's QoL, especially with regard to disease effect on activity limitation [18,19]. These data further contribute to increasing evidence that caregiver reports cannot be used in place of a child's report about disease-specific QoL [20].…”
Section: Quality Of Lifementioning
confidence: 99%
“…The same result was found on two studies, one done to validate the Arabic version of the PAQLQ (20) and another at Ain Shams University. (23) On the other hand, another studies carried on asthmatic children at Sweden, (25) Poland, (31) Brazil (22) and Jordon (26) that the score of activity limitation was the most affected one. Our study showed that there was a significant positive correlation between FEV1 and overall PAQLQ score.…”
Section: Discussionmentioning
confidence: 99%